Emergence of a new epidemic/epizootic Venezuelan equine encephalitis virus in South America. - Rico-Hesse, R (1995)
One of the most important questions in arbovirology concerns the origin of epidemic Venezuelan equine encephalitis (VEE) viruses; these viruses caused periodic, extensive epidemics/epizootics in the Americas from 1938-1973 (reaching the United States in 1971) but had recently been presumed extinct. We have documented the 1992 emergence of a new epidemic/epizootic VEE virus in Venezuela. Phylogenetic analysis of strains isolated during two outbreaks indicated that the new epidemic/epizootic virus(es) evolved recently from an enzootic VEE virus in northern South America. These results suggest continued emergence of epizootic VEE viruses; surveillance of enzootic viruses and routine vaccination of equines should therefore be resumed.